Defined geometry of binding between triantennary glycopeptide and the asialoglycoprotein receptor of rat heptocytes. - Kevin G. Rice; Ora A. Weisz; Thomas K. Barthel; Reiko T. Lee; Y C Lee (1990)
Three derivatives of a triantennary glycopeptide, each containing a single uniquely located 6-amino-galactose residue at either position 6', 6, or 8, were modified at the 6-amino group by attachment of a photolyzable reagent and radiolabeled by iodination of tyrosine. These were allowed to bind to the asialoglycoprotein receptor of isolated rat hepatocytes and photolyzed for affinity labeling. (formula; see text) Each probe specifically labeled either the major (RHL1) or minor (RHL2/3) subunits which comprise the receptor. A photolyzable group attached to galactose residue 6 6' specifically radiolabeled RHL1, whereas a photolyzable group attached to galactose 8 specifically labeled RHL2/3. Photoaffinity labeling of a soluble rat hepatic lectin preparation demonstrated that the minor subunits (RHL2/3) were no longer labeled by the triantennary probe with a photolyzable group at galactose 8. The inhibitory potency of a variety of complex glycopeptides against radiolabeled ligand binding to both rat hepatocytes and soluble lectin are in agreement with photoaffinity results that galactose 8 of triantennary glycopeptide is of unique importance by binding solely to the minor subunits (RHL2/3) of the asialoglycoprotein receptor on hepatocytes. Conversely, galactose residues 6 and 6' bind specifically to the major subunit (RHL1), indicating a precise binding geometry between the trivalent ligand and lectin.